Efektivitas Bimbingan Kelompok Teknik Psikodrama Untuk Meningkatkan Kepercayaan Diri Siswa di SMP N 09 Sungai Durian Kabupaten Solok Selatan - Rahmadani, Sri Sinta (Kognitif: Jurnal Pendidikan dan Inovasi Pembelajaran, 2025)
This study was motivated by the phenomenon of students who are unsure of their ability to answer questions when taking exams, who are unsure of their ability to answer questions posed by teachers, who are unable to express their opinions in group discussions because they feel unsure of their abilities, and who cheat on exams because they are unsure of the answers they have given. Self-confidence is recognizing oneself, both behaviorally and emotionally, and having motivation that comes from within, doing everything in accordance with good self-confidence. Self-confidence arises from within a person to provide a sense of certainty that what they are doing can be achieved. To overcome self-confidence issues in the field, researchers implemented psychodrama techniques in group counseling. This study aims to determine the effectiveness of group counseling using psychodrama techniques to increase the self-confidence of seventh-grade students at SMP N 09 Sungai Durian Solok Selatan. This study is a quantitative pre-experimental study using a one-group pretest-posttest design. The population consists of 29 seventh-grade students, while the sample consists of 10 students who lack self-confidence, selected using purposive sampling. The data collection instrument is a questionnaire. Data analysis techniques used nonparametric statistical tests using the Wilcoxon rank test (SPSS) version 22. The research results showed that the Z test (Wilcoxon) results indicated a difference between the pretest and posttest scores. The Wilcoxon test showed a significance p-value of -2.807. Based on the p-value threshold of 0.05, the Wilcoxon test p-value of 0.005 means that Ha is accepted and Ho is rejected. The Wilcoxon calculation results indicate that group guidance using psychodrama techniques is effective in increasing student confidence.